If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(q + -3) + 6 = 0 Reorder the terms: 2(-3 + q) + 6 = 0 (-3 * 2 + q * 2) + 6 = 0 (-6 + 2q) + 6 = 0 Reorder the terms: -6 + 6 + 2q = 0 Combine like terms: -6 + 6 = 0 0 + 2q = 0 2q = 0 Solving 2q = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Divide each side by '2'. q = 0 Simplifying q = 0
| 3-4(x+4)=6x-13 | | f(-2)=-8x-5 | | -6(n+3)+19=-2n-11 | | L=1/2pV^2SC | | 3.2+(h+5.1)= | | Y=(-1/5)-20-2 | | 45/B=15 | | -4-4s=-8-2s | | 63/60=x/180 | | 4a/3=160 | | y/6-3 | | 4x(4x-5b)+3= | | 3+3d= | | 9b^2-48b+48+15b^2-20b=20b-5b^2 | | 22v-9v-8v-v-3v-1=34 | | 100[0.03(p+9)]= | | -28=(4/5)d | | 3x-1+2x^2(6)= | | 7x-(3x-9)= | | 3y+17=-2y+24 | | -6d-10=-5d | | 6b-3b+4b-4b+1=25 | | x^2+y^2-2x+8y-23=0 | | -(5a+9)-5(a-8)= | | (2x+1)(2x-1)=y | | -2(z+3)-z+-z-4(z+2)= | | 2x+84=3.333333333 | | 0+.75x=7.5+.5x | | 2x+84=3 | | (2/3)t=9 | | 6b-3b+4b+1=25 | | -3g-3= |